Transmission of multidrug-resistant Mycobacterium tuberculosis in Wuhan, China: A retrospective molecular epidemiological study. Issue 4 (28th January 2022) - Duan, Qionghong; Zhang, Zhengbin; Tian, Dan; Zhou, Meilan; Hu, Yanjie; Wu, Jun; Wang, Tiantian; Li, Yuehua; Chen, Jun
Abstract : Abstract: How multidrug-resistant tuberculosis (MDR-TB) spreads and expands in Wuhan population is not clear. The study aimed to determine the transmission patterns of MDR-TB in Wuhan city, China, including 149 patients with MDR-TB. Tuberculosis isolates were genotyped by deletion-targeted multiplex polymerase chain reaction, mycobacterial interspersed repetitive unit-variable number tandem repeat typing, and sequencing of drug resistance-associated genes. The risk factors of genomic-clustering were analyzed with logistic regression. The genomic-clustering patients were deeply investigated. The analysis identified 111 unique and 11 clustered genotypes (38 isolates). The clustering rate was 25.50% and the minimum estimate proportion of recent transmission was 18.12%. Two clusters (5 isolates) shared the same mutation, the remain 9 clusters (33 isolates) had different mutation. Logistic regression showed that older than 60 years (adjusted OR 2.360, 95% CI:1.052-5.292) was an independent factor associated with the genomic-clustering of MDR-TB. Among the 38 genomic-clustering cases, 14 cases had epidemiological transmission links. The most common type of transmission link was social contact. The local transmission of MDR-TB in Wuhan was really an issue. The elderly population might be the high-risk groups for transmission of MDR-TB, and the community or public transportation might be the main transmission places.